Goethe and Schiller memorial in Weimar - Rietschel, Ernst, 1804-1861 (sculptor):::Creator::::::::::::; Hanfstaengl, Franz, 1804-1877 (photographer):::Contributor::::::::::::
Photomechanical print of a photograph by Hanfstaengl of the Goethe and Schiller monument by Rietschel, located in Weimar.